Risk factors for dental caries in adults aged 35-44 years in DKI Jakarta: a cross-sectional study using the 2018 national Riskesdas data - Kristanto, Cindy Vania; Theresia, Tiarma Talenta (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Caries, an oral cavity disease with several causes, is significantly increasing. According to the 2018 Basic Health Research, 92.2% of adults between the ages of 35 and 44 had dental caries. In DKI Jakarta, the prevalence of oral health issues reached a percentage of 59.1%. The purpose of this study was to determine the risk factors for dental caries in adults aged 35-44 years in DKI Jakarta. This research is descriptive observational research with a cross-sectional design. This research uses secondary data from the 2018 Riskesdas. The final total of the respondents was 1,100 after considering the inclusion and exclusion criteria. Based on the results of the research, respondents who were at higher risk of caries development were female (52.2%), employed (68.3%), and had intermediate education (46.3%). Based on certain habits, groups of risk factors that have a high frequency are incorrect time to brush teeth (97.2%), consuming sweet food 1-6x per week (48.5%), consuming sweet drinks ≥ 1x per day (64.3%), consuming soft drinks (89.6%) and energy drinks (93.9%) ≤ 3x per month, not consuming alcoholic beverages (96.8%), and smoking (51.9%). Overall, the prevalence of caries in adults aged 35-44 years in DKI Jakarta is 45%, with a high frequency of various risk factors. Risk factors that are related to the incidence of dental caries are intermediate level of education (OR = 1.19573), high level of education (OR = 1.58056), unemployed (OR = 0.78646), consumption of sweet foods ≥ 1x per day (OR = 0.71107), and smoking (OR = 0.72334).